Potensi Pemanfaatan Nilai Gizi Buah Eksotik Khas Kalimantan Selatan - Susi Susi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2014)
Indonesia is now importing the fruits in quantities large enough to meet food needs, but each region in Indonesia has the potential of local fruit with high nutritional value. South Kalimantan is one of the areas rich in biological resources, including exotic fruits. Exotic fruits have not been widely known and most have not been used optimally. Based on its chemical characteristics of South Kalimantan's exotic fruits show potential for development as refined products in order to develop agroindustry and also for the development of functional food sources that are beneficial to health. Fruit is examined in this study include kasturi, mangosteen, balangkasua, kapul, kakalayu, ramania, gitaan mata kucing and katiau. Preliminary analysis conducted on nutrition of fruit, including analysis of water content, fat, protein, ash, fiber, carbohydrates, total acid, and vitamin C. Test results showed the typical exotic fruits contain fiber and vitamin C is quite good, the fruits can be studied further as a source of functional food. Most of the fruit pulp at small amount and hard to eat so there is potential for utilization as well the skin and seeds of fruit.